2004
DOI: 10.1080/15421400490479280
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Quaternary Ammonium and Phosphonium Salts Bound to Macromolecular Supports for Removal Bacteria from Water

Abstract: This paper deals with synthesis and characterization of mixed quaternary ammonium and phosphonium salts grafted on macromolecular supports by polymer-analogous trans-quaternization reactions. The degrees of functionalization with quaternary mixed ammonium and phosphonium groups are relatively high, ranging from 0.09 to 1.285 mmoles of functional groups=gram of copolymer, ensuring a sufficient concentration of active centers per unit mass of copolymer and being well suited for application as antibacterial agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…17-21 Popa et al 22,23 reported the synthesis of quaternary ammonium and phosphonium salts grafted on cross-linked polymer-supports and their application as antibacterial agents for removal of bacteria from water. Although several types of soluble and insoluble antibacterial monoquats were reported, they suffer from lower activity and irritant side effects because of the availability of a single quaternary ammonium group.…”
Section: Introductionmentioning
confidence: 99%
“…17-21 Popa et al 22,23 reported the synthesis of quaternary ammonium and phosphonium salts grafted on cross-linked polymer-supports and their application as antibacterial agents for removal of bacteria from water. Although several types of soluble and insoluble antibacterial monoquats were reported, they suffer from lower activity and irritant side effects because of the availability of a single quaternary ammonium group.…”
Section: Introductionmentioning
confidence: 99%
“…1) are effective coatings for commercial water filtration membranes that resist protein adsorption under static exposure and dynamic flow conditions. Phosphonium-and ammonium-functionalized polymers have previously been used as biocides to remove bacteria and living organisms from surfaces [46,47]; however, they have not been studied for resisting non-specific protein adsorption. Only one example of a tetra(alkyl)ammonium-functionalized SAM has been previously explored for protein resistance and exhibited only mediocre results [29].…”
Section: Introductionmentioning
confidence: 99%
“…FTIR spectra of he obtained mixed ammonium and phosphonium resins [37] shown the presence of mixed ammonium and phosphonium groups on the surface of styrene-divinylbenzen copolymer support. The decrease in the intensity of the chloromethyl absorption bands at 1260 cm -1 and 1430 cm -1 suggests that a direct quaternization of the residual chloromethyl groups of the initial copolymer also took place, along with the main reaction of transquaternization of the quaternary ammonium groups.…”
Section: Resultsmentioning
confidence: 98%
“…Mixed ammonium and phosphonium salts grafted on a styrene -7 % divinylbenzene copolymer (Scheme 2) were obtained by Michaelis-Becker polymer analogue reaction [37].…”
Section: Functionalization Of Macromolecular Supports With Phosphonatmentioning
confidence: 99%